Work performance of middle-aged and elderly employees in hotel industry: the moderating effects of organizational support and age discrimination - Chow, Wen Wei; Peng, Pai (Frontiers in Psychology, 2025)
With the acceleration of the process of social aging, the re-employment of middle-aged and elderly people has gradually attracted the attention of society. Due to the relatively low barrier to entry, the hotel industry is favored by middle-aged and elderly people who are re-employed. This study analyzes the impacts of the three-dimensional capital on the job performance of middle-aged and elderly employees and investigates how organizational support and age discrimination moderate the effect of job satisfaction on job performance. A self-administered questionnaire was distributed to 400 hotel employees using convenience sampling. First, the three-dimensional capital has a positive impact on the job performance of both middle-aged and elderly employees; second, Job satisfaction has a mediating effect between the three-dimensional capital and the job performance of middle-aged and elderly employees; third, perceived organizational support positively moderates the effect of job satisfaction on job performance of middle-aged and elderly employees, and age discrimination perception negatively moderates the effect of job satisfaction on job performance of middle-aged and elderly employees. Theoretical and practical implications, as well as limitations and future research directions, are discussed.